Assessment of electric power quality electrical avionics systems of modern aircraft in ground conditions - Ильенко, С. С. (Problems of Informatization and Control, 2013)
Treatment of the problem is to estimate the quality of electric power in accordance with the requirementsof constantly rising standard technical documents ICAO and increase the efficiency of electricalsystems, avionics in terrestrial laboratory, operational bench testing and debugging. Assessment ofthe quality of electric power of modern aircraft and regulated by the applicable standards provided inthe design for the subsequent stages of certification, the normal production and operation.